PENGARUH MINUMAN JUS BUAH TERHADAP PERUBAHAN DERAJAT KEASAMAN (pH) SALIVA - Disi Raudatul Janah; Widodo Widodo; Rosihan Adhani (Universitas Lambung Mangkurat, 2021)
ABSTRACTBackground: Caries is a hard tissue disease of teeth, namely enamel, dentin and cementum, which is caused by an activity of a microorganism in a carbohydrate. The cause of the mainstay of the teeth is a factor, which is caused by mineral substances with nutrients rich in carbohydrates. One of the predisposing factors for dental caries is drinking. Drinks that can cause a decrease in the acidity (pH) of saliva are drinks that contain sugars such as fructose, glucose, sucrose, citric acid and ascorbic acid. Methods: All articles reviewed were obtained from searches for data sources Google Scholar, and Science Direct which had a range maximum journal publication time in the last 10 years. Results: The review was conducted on 12 journals which were found to fit the inclusion criteria, such as journals available in full text form and research subjects fruit juice which is often consumed by the public. Conclusion: there is a decrease in salivary pH after consuming fruit juice. Keywords: acidity, fruit juice, pH of saliva. ABSTRAK Latar Belakang: Karies merupakan suatu penyakit jaringan keras gigi, yaitu email, dentin dan sementum, yang disebabkan oleh aktivitas suatu jasad renik dalam suatu karbohidrat. Penyebab terjadinya karies gigi dipengaruhi beberapa faktor, seperti disebabkan zat mineral dengan dominan nutrisi kaya akan karbohidrat. Faktor predisposisi karies gigi salah satunya adalah minuman. Minuman yang dapat menyebabkan turunnya derajat keasaman (pH) saliva adalah minuman yang mengandung gula seperti fruktosa, glukosa, sukrosa, asam sitrat dan asam askorbat. Metode: Semua artikel yang direview diperoleh dari pencarian sumber data Google Scholar, dan Science Direct yang memiliki rentang waktu penerbitan jurnal maksimal 10 tahun terakhir. Hasil: Review dilakukan pada 12 jurnal yang ditemukan sesuai dengan kriteria inklusi seperti jurnal tersedia dalam bentuk full-text dan subjek penelitian jus buah yang sering dikonsumsi masyarakat. Kesimpulan: terjadi penurunan pH saliva setelah minum jus buah. Kata kunci: derajat keasaman, jus buah, pH saliva.